An epistemological analysis of the concept of quotient group - Nguyen , Ai Quoc (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
In the history of group theory, the quotient group is considered to be fundamental to the study of groups. The concept’s development of quotient group is closely linked with the abstraction of group theory. This paper presents an epistemological analysis of the history of the development and formation of the “standard definition” of quotient group, which helps determine the epistemological characteristics and the obstacles for students in learning the quotient group.